Concevoir un living book en sciences humaines et sociales : retour d’expérience - Martine Clouzot; Marie-José Gasse-Grandjean (Humanités Numériques)
The “living book”, a new format from the Life Sciences, made it possible to take stock of a subject, to highlight a corpus of images, an advanced research and a bibliography. This hybrid, Web-oriented format is re-positioning the producer, the user and the technology. In a simple, lean and rigorous apparatus, it allows to organise a diverse and growing mass of documentation (texts, images, audio, websites). It proposes new ways of writing (collaboration, short texts, summaries) and structuring the contents. It promotes networking and contacts with libraries and museums while drawing attention to formats, licences and rights. It suggests individualised reading paths, reaching diverse audiences. We wanted to give testimony of our experience, since the living book is an editorial and intellectual, hybrid, collaborative, creative, aggregative, accessible, and open device which modified the production, valorisation and diffusion of our research.